A Study of Prevalence of Piriformis Syndrome in Long Route Bike Riders - Tukare, Vinayak Annappa; Bavalekar, Namrata Mahesh; Kurale, Vinayak Shankar; Wangate, Krishika Baban (Journal of Neonatal Surgery, 2025)
Introduction: Piriformis syndrome is a condition caused by prolonged or excessive contraction of piriformis muscle with entrapment of sciatic nerve. In long route motorcycling the rider will sit constantly in the same posture throughout his ride. Prolonged sitting in the same posture can lead to restriction of blood and can cause distress to the body which leads to muscle stiffness and discomfort. This can lead to various musculoskeletal disorders often called as driving related musculoskeletal disorders. Methodology: Ethical clearance was obtained from Institution Ethical Committee. Total 205 participants were included in this study according to the inclusive criteria; Participants were diagnosed through two test Modified FAIR test and Sitting piriformis stretch test. The intensity of pain was rated through Numeric Pain Rating Scale. Result: A total of 205 long-route bike riders participated in the study. Among them, 108 individuals tested positive for the piriformis test, indicating a prevalence rate of 52%. Conclusion: This study identified a 52% prevalence of piriformis syndrome among long-route bike riders. Further analysis showed that affected riders covered a mean riding distance of 800 km, suggesting that prolonged riding duration contributes to the development of piriformis syndrome.